Cyberattacks on the Financial Sector of Critical Infrastructure (International Journal of Contemporary Security Studies, 2024)
The financial sector of critical infrastructure represents one of the most vulnerable sectors when it comes to cyber attacks, due to its crucial role in the global economy and the nature of business today. The digitalization of finance opens the door to cyber attacks through the wide and pervasive availability of financial services on modern technologies and networks. This paper explores protective measures against cyber attacks in the financial sector by analyzing three significant incidents: the attack on the Central Bank of Bangladesh, the data breach at Capital One, and the ransomware attack on Travelex, a money transfer company. The primary aim of the research is to analyze the impact of cyber attacks on the financial sector of critical infrastructure and to identify effective protective measures that can reduce the risk of similar attacks in the future. By utilizing a review of international literature and case studies, the paper emphasizes the importance of integrating technological and organizational measures, as well as the significance of building cyber resilience through continuous improvement of security protocols and a culture of cyber awareness. The research findings indicate that while cyber attacks pose significant risks, they can also drive financial institutions toward innovation and enhancement of protective measures.
Keywords: srpski